Model Pengelolaan Sampah Organik Terintegrasi Budidaya Magot: Pendampingan KSM Buruan Sae RW 03-4 Pakemitan - Muhamad Hidayat; Farid Arifin; Dudi Yudha Kusuma; Mochamad Lutfi Wijoyo; Heldiansyah (LPPM Universitas Langlangbuana, 2026)
This community service program designs and implements agains the organic waste management and integrated with cultivation Black Soldier Fly (BSF) through mentoring of Community Self-Help Groups (KSM) Buruan Sae in RW 03–04, Pakemitan Village, Cinambo District, Bandung City. Interventions included strengthening sorting practices at source, transferring non-technical knowledge (group management, record keeping, marketing), developing simple operational modules and operationalization procedure system (OPS), demonstrating maggot cultivation, and facilitating maggot product marketing networks. The research used a participatory qualitative approach: participant observation, interviews, Focus Group Discussions (FGDs), and visual documentation. Initial findings indicated increased awareness and intention to sort at the household level, the establishment of pilot-scale cultivation units managed by community, the development of operational modules and or OPS, and the opening of local market access for maggot products and compost. The developed model emphasized local circular economy principles, simple record keeping for community business management, and a yield based financing mechanism. Recommendations included strengthening quantitative monitoring, implementing incentive schemes for sorters, and providing further technical assistance to stabilize product quality.